2023
DOI: 10.3390/buildings13030806
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing PCM Integrated Wall and Roof for Energy Saving in Building under Various Climatic Conditions of Mediterranean Region

Abstract: Energy conservation in buildings has been the focus of many studies since nearly one-third of global energy consumption is due to buildings. Phase change material (PCM) technology promises to be an attractive solution for energy saving in buildings since it is a passive and effective technology, as demonstrated in the literature. Therefore, this study focuses on the energy-saving performance of PCM-integrated buildings located in a Mediterranean climate to reveal their energy-saving potential. PCM is integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…For the heating design, the most efficient PCM is RT22, characterized by a lower mean transition temperature of 22 • C. On the other hand, for the cooling design, the most effective PCM is RT28, defined by a higher mean transition temperature of 28 • C. The highest possible seasonal thermal load energy savings are achieved with a PCM defined by a mean transition temperature similar to the building's seasonal indoor temperature setpoint. This conclusion is validated by the study of Dardouri et al [18], who focused their study on various locations of Mediterranean climatic conditions in Tunisia and calculated that a PCM with a lower melting temperature of 21 • C is more effective for maximizing heating energy savings, while a PCM with a higher melting temperature of 29 • C allows higher cooling energy savings. Additionally, the increase in the PCM's thickness allows the reduction of the cumulative electricity demand for heating and cooling, with the reduction ranging from 5.65% to 13.55%.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For the heating design, the most efficient PCM is RT22, characterized by a lower mean transition temperature of 22 • C. On the other hand, for the cooling design, the most effective PCM is RT28, defined by a higher mean transition temperature of 28 • C. The highest possible seasonal thermal load energy savings are achieved with a PCM defined by a mean transition temperature similar to the building's seasonal indoor temperature setpoint. This conclusion is validated by the study of Dardouri et al [18], who focused their study on various locations of Mediterranean climatic conditions in Tunisia and calculated that a PCM with a lower melting temperature of 21 • C is more effective for maximizing heating energy savings, while a PCM with a higher melting temperature of 29 • C allows higher cooling energy savings. Additionally, the increase in the PCM's thickness allows the reduction of the cumulative electricity demand for heating and cooling, with the reduction ranging from 5.65% to 13.55%.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, Jayalath et al [17] concluded that a PCM roof layer with a mean transition temperature of 23 • C can lead to a 39% reduction in energy consumption for cooling and a 12% reduction in energy consumption for heating for a one-story residential building in Melbourne. Regarding various areas with a Mediterranean climate, Dardouri et al [18] calculated that the modulation of the PCM layer on the roof has an immediate effect on the building's thermal loads, leading to a cumulative energy reduction in the range of 8% to 31.5%.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the use of the PCM elements with doubled-layer provided lower energy consumption than the single-layer one, specifically in warm-arid regions [2]. This highlights the importance of the number of PCM layers, location, and thickness.…”
Section: Introductionmentioning
confidence: 96%
“…The simulation results showed that adopting PCM layouts in conjunction with ventilation can increase the thermal performance of the thermal comfort conditions during the hotter seasons. Using PCM with a melting temperature of 21℃ has preferred heating energy savings, while PCM with 29℃ melting temperature has better cooling energy savings as reported by Dardouri et al [2]. An advanced nanoparticle improved PCM (nano-PCM) was developed by Biswas et al [24].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation